2005
DOI: 10.1051/0004-6361:20041817
|View full text |Cite
|
Sign up to set email alerts
|

Convection-pulsation coupling

Abstract: Abstract. We apply here the Time Dependent Convection (TDC) treatment presented in our earlier paper in this series to the study of δ Sct and γ Dor pulsating stars. Stabilization of the δ Sct p-modes at the red edge of the Instability Strip (IS) and the driving of the γ Dor g-modes are explained by our models. Theoretical IS obtained with different values of the Mixing Length (ML) parameter α are compared to observations and a good agreement is obtained for α between 1.8 and 2. The influence of each term of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
354
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 297 publications
(381 citation statements)
references
References 22 publications
25
354
2
Order By: Relevance
“…Of the sixteen δ Sct stars, Scuflaire et al 2008). The input physics included is similar to the one used in Dupret et al (2005) with the following values for the modelling parameters α MLT = 1.8, α ov = 0.2 and Z = 0.02. The solid thick black and light grey lines mark the blue and red edge of the observed instability strips of δ Sct and γ Dor stars, as described by Rodríguez & Breger (2001) and Handler & Shobbrook (2002), respectively.…”
Section: Characterization Of Stars That Show No Clear Periodic Variabmentioning
confidence: 99%
“…Of the sixteen δ Sct stars, Scuflaire et al 2008). The input physics included is similar to the one used in Dupret et al (2005) with the following values for the modelling parameters α MLT = 1.8, α ov = 0.2 and Z = 0.02. The solid thick black and light grey lines mark the blue and red edge of the observed instability strips of δ Sct and γ Dor stars, as described by Rodríguez & Breger (2001) and Handler & Shobbrook (2002), respectively.…”
Section: Characterization Of Stars That Show No Clear Periodic Variabmentioning
confidence: 99%
“…At these temperatures, the interaction between convection and pulsation described by Grigahcène et al (2005) and Dupret et al (2005) may change the non-adiabatic eigenfunctions significantly.…”
Section: Amplitude Ratios Vs Phase Differencesmentioning
confidence: 99%
“…These A-and F-type Appendices A and B are available in electronic form at http://www.aanda.org stars are pulsating with high-order, non-radial g-modes (Guzik et al 2000;Miglio et al 2008). Theoretical stability analyses adopting time-dependent convection predict an instability strip (IS) to occur close to where γ Dor are observed, involving a fluxblocking excitation mechanism (Guzik et al 2000;Dupret et al 2005). However, Dupret et al (2004) showed that the agreement between observations and theory depends very sensitively on the exact treatment of convection.…”
Section: Introductionmentioning
confidence: 99%